Mapping Leisure Studies from Australia, Asia and Africa (Springer Singapore, 2018)
This volume addresses the rich and varied thoughts, concepts, approaches and leisure practices in sixteen countries of three continents---Australia, Asia and Africa. The chapters showcase the diversity in the forms and ways in which the idea and practice of leisure have developed across space and time. However, the common thread through the chapters is that concepts and practices of leisure are found all over the world, from pre-historic settlements to the present-day consumer societies. Seemingly, being at leisure is a capacity of the human species present at birth and which develops in a variety of individual and societal contexts. Even in situations where leisure gets little official recognition as being an aspect of life---such as under colonial rule or in extremely work-centric societies---it needs to be contextually understood. This is a welcome addition to the literature on leisure studies from a global and comparative perspective. .